Understanding children’s food-related emotions using words and emojis in the United States and Ghana - Gallo, Katherine Elizabeth (Kansas State University, 2016)
Although consumer emotions have recently become a popular research area in the sensory and consumer sciences, there remains a need for an approach designed to evaluate children’s food emotion experience. The objective of this research was to understand U.S. and Ghanaian children’s emotion responses to food, using words and emojis. In the first part of the research, focus groups were conducted to understand children’s use of emotion words and emojis in response to an array of food consumption experiences, both real and recalled. Through this study, a narrowed list of appropriate words and emojis was identified for further testing with children. This study also revealed that children readily use both emotion words and emojis to characterize their food experiences. The next phase of the research was conducted in three parts, which each included emotion assessments of children’s favorite and disliked foods, as well a common set of eight products selected to elicit a broad range of emotions. First, the emotion set identified in focus group testing was used by children in the United States to assess pictures of foods. The responses from this study were used to further narrow the list of appropriate emojis and emotion words. Second, the reduced emotion set was used by children in the U.S. to assess appearance and post-taste emotions for the products. Finally, a food image test with the reduced emotion set was conducted in Accra, Ghana with schoolchildren. Fielding in Ghana allowed for an exploration of the considerations sensory researchers must make when conducting cross-cultural research with children. Emotion word and emoji usage was similar between U.S. and Ghanaian participants, although some differences were observed. The U.S. studies were compared, revealing the influence of stimulus type on children’s reported emotions. Results from the actual food experiences (appearance, taste) were more positive compared to the evaluation of images. Finally, among Ghanaian and U.S. children, high frequencies of selection for positive emotion words and emojis aligned with a favorite food experience. Overall, this research introduces a new approach to consumer emotion research with children for use both domestically and abroad.
Keywords: Food science; Consumer research; Children; Emotion; Emoji; Cross-cultural research